2018
DOI: 10.20546/ijcmas.2018.712.416
|View full text |Cite
|
Sign up to set email alerts
|

Bio efficacy of New Insecticide Molecules Chlorantraniliprole 35% WG against Sugarcane Early Shoot Borer Chilo infuscatellus (Snellen) and Internode Borer Chilo sacchariphagus indicus (Kapur)

Abstract: The varied dosages of Chlorantraniliprole 35%WG in comparison with different insecticides were tested along with untreated check using randomized block design with three replications. Significant differences were noticed among the treatments. Among the different insecticides evaluated. Drenching the sets immediately after planting in furrow with Chloranthriniliprole 35%WG @ 88 gai/ha and Chloranthriniliprole 35%WG @ 75 gai/ha, were proved superior by recording lowest average per cent dead hearts by early shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In a study, it is found that Chlorantraniliprole 35%WG @ 75 g a.i. /ha were found effective in reducing Internode borer damage (Sunilkumar et al, 2018). This result was similar to the present findings also.…”
Section: Resultssupporting
confidence: 93%
“…In a study, it is found that Chlorantraniliprole 35%WG @ 75 g a.i. /ha were found effective in reducing Internode borer damage (Sunilkumar et al, 2018). This result was similar to the present findings also.…”
Section: Resultssupporting
confidence: 93%
“…is effective [43]. Syrphid fly @ 1000 larvae or cocoons per ha [44]. Internode borer will be managed by releasing Trichogramma chilonis parasitized eggs in suitable instalments and the use of pheromone traps.…”
Section: Ipm Approachesmentioning
confidence: 99%